Investigation of Beam Width Shaping of a Ku-band Horn Antenna using a Diffractive Optic Element and an Electromagnetic Wave Absorber - Ahmet Teber (Sakarya Üniversitesi Fen Bilimleri Enstitüsü Dergisi)
The feasibility of beam-shaping of a Ku-Band horn as a transmitting (Tx) antenna by mounting two different versions of lenses which are kind of Fresnel Zone Plates (FZP) is studied. The designed and fabricated geometrical structures offer a simpler approach building Fresnel Zone Plates by using an electromagnetic wave absorber and diffractive optic material. The diffractive optic material, paraffin, forms a set of alternating open and opaque annular zones on a flat surface, based on the design principles of Fresnel Zone Plates. An electromagnetic wave absorber covers the top surface of the formed paraffin, but not including the grooves. Thereafter, the Fresnel Zone plates are suitably attached in front of the transmitter horn antenna, located in the far-field region of a receiving antenna. The half-power beam-widths for the horn antenna (unloaded) and with two types of lenses are investigated. The results indicate that Fresnel zone plate structures can play a role suppressing side lobes in H-plane so that the effective radiation is to be significantly concentrated.